(untitled) (Research, Society and Development, 2020)
Introduction: Oronasal communications are conditions in which there is direct access to the oral cavity, either through the alveolar ridge or the palate, with the maxillary sinus. When it is covered by epithelial tissue, it is referred to as oronasal fistula. Its etiology can come from extractions, pathologies in the palate, periapex and maxillary sinus, infections, osteonecrosis, and trauma. The signs and symptoms that are observed range from the passage of air and fluids from the nose to the mouth, and vice versa, to acute or chronic sinusitis, with the possibility of being asymptomatic in some cases. Its diagnosis is reached with the physical/clinical examination, associated with imaging tests. Usually, the treatment consists of a surgical approach, which should be performed as soon as possible, and the surgical techniques and types of flaps used vary according to the type of communication. Case report: Patient victim of a gunshot wound for about 04 years, evolving with oronasal communications of dimensions approximately 02cm X 01cm (length X width), reaching the alveolar ridge. The treatment performed was through surgery to correct/close oronasal communications in a hospital environment with the association of three techniques. Discussion: The surgical techniques used to close communications and oronasal fistulas are basically the three most used, each presenting advantages and disadvantages, as well as the best indication for each case. The Bichat’s ball is considered the most used technique, presenting as a disadvantage, the possible reduction of the vestibule bottom, thus hindering posterior prosthetic rehabilitation, such as the vestibular flap. Palatal flaps are more indicated when communications are more extensive, their disadvantages include the raw area exposed on the palate when the flap needs to be rotated. Conclusion: The case report differs from the others found in the current literature due to the association of surgical techniques used to close buccal sinus fistulas, and the benefits that the association of these brought to the patient.